Digital mental health apps for self-management of depression: a scoping exploration on awareness, attitude, and user experience among professional course students - Sucharitha, Sree T.; Manoharan, Aravind; Dhanuraja, Velusamy; Kasi, Arunadevi; Ezhilarasan, Suganya (International Journal Of Community Medicine And Public Health, 2020)
Background: Globally, depressive disorders are ranked as the single largest contributor to non-fatal health loss (7.5% of all years lost due to disability-YLD). In India, provision of quality mental health care services remains a challenge due to severe deficiency of qualified care givers. Harnessing the potential of digital technologies and smart phone apps need to be explored to address the existing gaps in mental health care services. This study aims to describe the awareness, attitudes and user experiences of mental health apps among professional course students. Methods: A mixed-methods study methodology was adapted involving medical professional students of a tertiary teaching hospital in South India. A web-based survey assessed the awareness, attitudes and usage of mental health apps. Further, in-depth interviews (30) were conducted among selective app users (20) and non-users (10) to gain insights about the user experiences. Results: Among 898 respondents for the web-based survey, majority were female (513,57.1%), aged between 18-25 years (801,89.2%) undergraduates (673,74.9%), undertaking professional courses in medicine and allied health sciences (633,70.6%). 273 (30.4%) respondents were aware of apps and 86 (9.6%) were ever users. Novel interactive platforms, privacy and agency for self-care are the major factors for using the apps however data confidentiality and authenticity of the app-based information were identified as major concerns limiting app usage. Conclusions: The study found the utilization of mental health apps as self-management tool for depression gaining slow traction among professional course students.